The Type IVa Pilus Machinery Is Recruited to Sites of Future Cell Division - Tyson Carter (American Society for Microbiology, 2017)
ABSTRACT Type IVa pili (T4aP) are ubiquitous microbial appendages used for adherence, twitching motility, DNA uptake, and electron transfer. Many of these functions depend on dynamic assembly and disassembly of the pilus by a megadalton-sized, cell envelope-spanning protein complex located at the poles of rod-shaped bacteria. How the T4aP assembly complex becomes integrated into the cell envelope in the absence of dedicated peptidoglycan (PG) hydrolases is unknown. After ruling out the potential involvement of housekeeping PG hydrolases in the installation of the T4aP machinery in Pseudomonas aeruginosa, we discovered that key components of inner (PilMNOP) and outer (PilQ) membrane subcomplexes are recruited to future sites of cell division. Midcell recruitment of a fluorescently tagged alignment subcomplex component, mCherry-PilO, depended on PilQ secretin monomers—specifically, their N-terminal PG-binding AMIN domains. PilP, which connects PilO to PilQ, was required for recruitment, while PilM, which is structurally similar to divisome component FtsA, was not. Recruitment preceded secretin oligomerization in the outer membrane, as loss of the PilQ pilotin PilF had no effect on localization. These results were confirmed in cells chemically blocked for cell division prior to outer membrane invagination. The hub protein FimV and a component of the polar organelle coordinator complex—PocA—were independently required for midcell recruitment of PilO and PilQ. Together, these data suggest an integrated, energy-efficient strategy for the targeting and preinstallation—rather than retrofitting—of the T4aP system into nascent poles, without the need for dedicated PG-remodeling enzymes. IMPORTANCE The peptidoglycan (PG) layer of bacterial cell envelopes has limited porosity, representing a physical barrier to the insertion of large protein complexes involved in secretion and motility. Many systems include dedicated PG hydrolase components that create space for their insertion, but the ubiquitous type IVa pilus (T4aP) system lacks such an enzyme. Instead, we found that components of the T4aP system are recruited to future sites of cell division, where they could be incorporated into the cell envelope during the formation of new poles, eliminating the need for PG hydrolases. Targeting depends on the presence of septal PG-binding motifs in specific components, as removal of those motifs causes delocalization. This preinstallation strategy for the T4aP assembly system would ensure that both daughter cells are poised to extrude pili from new poles as soon as they separate from one another.